The CENP-A chaperone Scm3 becomes enriched at kinetochores in anaphase independently of CENP-A incorporation - Luconi, Lucia; Araki, Yasuhiro; Erlemann, Sarah; Schiebel, Elmar (Cell cycle, 2011)
Centromeres are specialized chromatin domains where kinetochores assemble. Centromeres contain as a conserved feature nucleosomes that are composed of the canonical histones H2A, H2B and H4 and a centromere-specific histone H3 variant, known as CENP-A in humans and Cse4 in budding yeast. The incorporation of CENP-A homologs into centromeric chromatin is cell cycle regulated and is assisted by related assembly factors named Scm3 in yeast and HJURP in human cells. Here, we describe that the budding yeast Scm3 binds weakly to centromeres during interphase including S phase when Cse4 assembles into centromeres. In anaphase Scm3 then becomes 2.5-fold enriched at kinetochores where it is dynamic with a half recovery time t½ of 36 sec. In contrast, Cse4 is stably integrated into kinetochores. In addition, ten Scm3 molecules bind to a cluster of 16 kinetochores with 32 Cse4 molecules suggesting a 1:3 ratio at kinetochores between the two proteins. Analysis of conditional lethal scm3-1 mutant cells indicated that Scm3 participates in maintaining Cse4 at centromeres in anaphase. Thus, Scm3 interacts transiently with kinetochores in anaphase where it safeguards Cse4 even after its S phase incorporation into centromeres.